Methic Arts: Cultural Preservation and Character Education Agent for the Community - Purwasih, Ririn; Thang, Ha Van; Arko, Benedict (Journal of Social Knowledge Education (JSKE), 2022)
Purpose of the study: This research aims to investigate the role of the community in preserving Methik Pari art, a traditional art form and a medium of character education, in Jeruk Village, Bandar District, Pacitan Regency. Methodology: This research uses a qualitative approach with the people of Jeruk Village as the subjects. The data collection techniques are observation, interview and documentation methods. The data analysis technique is triangulation, which involves comparing and cross-checking data from different sources and perspectives. Main Findings: Methik Pari art originated from a ritual tradition of expressing gratitude for the abundant harvest in the rice fields. Methik Pari art also embodies national character values such as religious values, hard work, environmental care, social spirit, curiosity, national spirit, discipline and responsibility, which can be used as an agent of character education for the Jeruk Village community. The community plays an important role in preserving Methik Pari art by participating in the creation, performance, and appreciation of the art form, as well as by passing on the character values to the younger generation. Novelty/Originality of this study: Methik Pari art as a traditional art form and a medium of character education in Jeruk Village, Pacitan Regency. The study also contributes to the existing knowledge in the field of art and culture education, by showing the uniqueness and social value of Methik Pari art and its role in preserving and developing the national character values of the local community.